2018
DOI: 10.2196/10228
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Phone–Based Healthy Lifestyle Monitoring Tool for People With Mental Health Problems (MyHealthPA): Development and Pilot Testing

Abstract: BackgroundPeople with mental health disorders live, on average, 20 years less than those without, often because of poor physical health including cardiovascular disease (CVD). Evidence-based interventions are required to reduce this lifespan gap.ObjectiveThis study aimed to develop, test, and evaluate a mobile phone–based lifestyle program (MyHealthPA) to help people with mental health problems improve key health risk behaviors and reduce their risk of CVD.MethodsThe development of MyHealthPA occurred in 3 sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However, only a quarter of participants reported that they would like to use the app frequently and most participants expressed neutral attitudes with regard to the app consistency and integration of features. Despite previous support for the effectiveness of mobile phone-based interventions for changing health risk behaviors [16][17][18][19][20], disparity between perceived acceptability of an app and actual use has been reported in previous mobile-based development and evaluation studies [40]. Co-design with young people and tools to promote active engagement are likely to be important components of any youth-based app.…”
Section: Principal Findingsmentioning
confidence: 93%
See 3 more Smart Citations
“…However, only a quarter of participants reported that they would like to use the app frequently and most participants expressed neutral attitudes with regard to the app consistency and integration of features. Despite previous support for the effectiveness of mobile phone-based interventions for changing health risk behaviors [16][17][18][19][20], disparity between perceived acceptability of an app and actual use has been reported in previous mobile-based development and evaluation studies [40]. Co-design with young people and tools to promote active engagement are likely to be important components of any youth-based app.…”
Section: Principal Findingsmentioning
confidence: 93%
“…The Health4Life app was based on our team's previously developed and evaluated multiple health behavior change mobile-based tool named MyHealthPA [40]. MyHealthPA was developed to help people improve 4 of the Big 6 lifestyle risk behaviors (poor diet, physical inactivity, alcohol use, and smoking).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the rapid development of mobile internet technology and growing prevalence of smartphones, mHealth has become an increasingly practical, innovative approach to health care delivery, especially in rural and remote areas [19-21]. Many applications for mHealth services have been reported in the extant literature, including chronic disease management [22,23], mental health services [24], health solutions for pregnant women and teenage youth [25-27], and health monitoring [28,29].…”
Section: Introductionmentioning
confidence: 99%